Reconsideration of indications for third hepatectomy for colorectal liver metastases. Issue 7 (10th August 2022) - Kimura, Jiro; Sui, Kenta; Murokawa, Takahiro; Tabuchi, Motoyasu; Sakamoto, Shinya; Iwata, Jun; Iiyama, Tatsuo; Okabayashi, Takehiro
Abstract: Background: It is unclear which patients with recurrence after a second hepatectomy will benefit from a third hepatectomy. Methods: Patients who underwent hepatectomy for colorectal liver metastasis (CRLM) between April 2005 and July 2021 were included. Factors affecting recurrence after each hepatectomy were analyzed. Results: Sixty‐four of the 167 patients who had recurrence after the first hepatectomy underwent a second hepatectomy. Then, 46 patients had recurrence and 18 patients did not have recurrence after the second hepatectomy. Sixteen patients who underwent a third hepatectomy had better overall survival (OS) than those who did not (52 vs. 31 months, p  = 0.043). However, the multivariate analysis demonstrated that only tumor size (>5 cm) during the second hepatectomy ( p  = 0.022) and carbohydrate antigen 19‐9 (CA 19‐9) level (>50 U/ml) ( p  = 0.041) at recurrence after the second hepatectomy were poor prognostic factors for OS. Conclusion: While a third hepatectomy can be performed if it is technically and oncologically appropriate, tumor size >5 cm and CA 19‐9 >50 U/ml should be considered in terms of long‐term outcomes before proceeding to surgery.